Comparison of multiple genotyping methods for the identification of the cancer predisposing founder mutation p.R337H in TP53 - Mariana Fitarelli-Kiehl; Gabriel S. Macedo; Rosane Paixão Schlatter; Patricia Koehler-Santos; Ursula da Silveira Matte; Patricia Ashton-Prolla; Juliana Giacomazzi (Genetics and Molecular Biology, 2016)
Abstract Germline mutations in the TP53 gene are associated with Li-Fraumeni and Li-Fraumeni-Like Syndromes, characterized by increased predisposition to early-onset cancers. In Brazil, the prevalence of the TP53-p.R337H germline mutation is exceedingly high in the general population and in cancer-affected patients, probably as result of a founder effect. Several genotyping methods are used for the molecular diagnosis of LFS/LFL, however Sanger sequencing is still considered the gold standard. We compared performance, cost and turnaround time of Sanger sequencing, PCR-RFLP, TaqMan-PCR and HRM in the p.R337H genotyping. The performance was determined by analysis of 95 genomic DNA samples and results were 100% concordant for all methods. Sequencing was the most expensive method followed by TaqMan-PCR, PCR-RFLP and HRM. The overall cost of HRM increased with the prevalence of positive samples, since confirmatory sequencing must be performed when a sample shows an abnormal melting profile, but remained lower than all other methods when the mutation prevalence was less than 2.5%. Sequencing had the highest throughput and the longest turnaround time, while TaqMan-PCR showed the lowest turnaround and hands-on times. All methodologies studied are suitable for the detection of p.R337H and the choice will depend on the application and clinical scenario.